Measuring Water Content in Hydroponic Plants Based on PH Values and Nutriens Using Fuzzy Logic Microcontroller Based Tsukamoto - Julianti, Miranda; Rakhmat Kurniawan R (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Hydroponic cultivation is a method of planting without soil by utilizing water containing nutrients and oxygen at certain levels. Regulation and monitoring of pH, nutrients (TDS), and water temperature are crucial factors in the success of a hydroponic system. Inaccuracies in nutrient water management can significantly affect plant growth. This study aims to design an automation system capable of monitoring pH and water nutrient levels using the Fuzzy Tsukamoto method based on the Nodemcu ESP32 microcontroller. The sensors used in this study are the MSP340 pH Module sensor to measure acidity (pH) and the Df Robot Module TDS sensor to detect nutrient levels in water. The Fuzzy Tsukamoto method is applied to make fuzzy logic-based decision-making, where the input values of pH and nutrients are converted into linguistic variables. The fuzzyfication process is carried out to determine the level of plant fertility, while the inference method is used to produce output based on previously set rules. This monitoring system also utilizes the Nutrient Film Technique (NFT) technique with a linear regression method to optimize the use of water pumps, making it more energy efficient. With the design of this system, hydroponic farmers can monitor water conditions automatically and in real-time, increasing efficiency and reducing human error in nutrient water management. The results of this study are expected to provide innovative solutions for the development of more efficient and sustainable hydroponic systems.